A PEMBELAJARAN KETERAMPILAN MENULIS TEKS EKSPOSISI DENGAN METODE QUANTUM LEARNING TYPE SHOW NOT TELL PADA SISWA KELAS X SMK PARIWISATA PABUARAN - Irpan Maulana; Neng Hilda Nurjamilah (STKIP Subang, 2022)
This research is motivated by problems contained in the learning to write exposition texts, namely: (1) Low skills in writing the exposition text of class X students at SMK Pariwisata Pabuaran. (2) Students have difficulty pouring ideas at the time of learning to write exposition texts. (3) Students lack understanding in determining the structure of exposition texts. Based on the background of the above problems, researchers formulated problems in this study, namely, (1) How the ability to write the text of the exposition of students of class X of SMK Pariwisata Pabuaran. (2) How is the ability to write the exposition text of class X students using the quantum learning type show not tell method. (3) How to improve the ability to write exposition text by using the quantum learning type show not tell method. (4) How class X students respond to learning to write exposition text with the quantum learning type show not tell method. The purpose of this research is: (1) Describing the ability to write exposition texts for students in class X of SMK Pariwisata. (2) Describe the ability to write exposition text of students of class X SMK by using the quantum learning type show not tell method. (3) Describe the increased ability to write exposition text using the quantum learning type show not tell method. The method used in this study uses pre-experimental and research design used in the form of experimental one group pretest-posttest design. This research was conducted at SMK Pariwisata Pabuaran with class X Ph 1 research subjects as an experimental class. Based on the results of statistical calculations obtained the average result of the initial test, which is 55.36 and the average score of the final test after using the quantum learning type show not tell method is 74.46. Based on these calculations, it can be known that there is an increase in the average initial test (pretest) and final test (posttest) which is 19.01%. Then it can be concluded that there is an increase in the learning of exposition text writing skills with the quantum learning type show not tell method in students of class X smk Pariwisata Pabuaran.